Effects of Euro area monetary policy on institutional sectors : the case of Portugal - Afonso, António (2017)
We study the effects of the euro area monetary policy on the institutional sectors in Portugal during the period 2000:4-2015:4. Our results show that the single monetary policy affected some variables that are proxies for the funding of each institutional sector of the economy: general government, other monetary financial institutions, non-financial corporations, households and the external sector. The period of the economic and financial adjustment programme influenced all institutional sectors, and financial integration in the euro area had an effect on the funding for the economy: there was a reduction of long term-to-GDP ratio, external funding to the Portuguese other MFIs, and new loans to households